Alcohol Fermentation Characteristics of Mixed Yeast Cultures - WANG Yuan, ZANG Yajie, XU Binyan, YANG Xueshan, ZHU Xia (Shipin Kexue)
To explore the effect of mixed culture fermentation with non-Saccharomyces yeast (NS) and Saccharomyces cerevisiae (S. cerevisiae) on oenological parameters and aroma compounds, a model grape juice was sequentially inoculated with pairwise mixtures of indigenous Torulaspora delbrueckii, Metschnikowia pulcherrima and Hanseniaspora uvarum followed by S. cerevisiae. The fermentation kinetics and changes in the volatile profile were analyzed. The results demonstrated that sequential fermentations with single (TV, MV and HV) and mixed NS (TMV, HMV and HTV) followed by Vintage white (VW) all reduced the content of ethanol and titratable acidity while increasing glycerol levels compared with pure S. cerevisiae fermentation (VW). In addition, the contents of esters, volatile fatty acids, carbonyl compounds, and volatile phenols significantly increased as determined by gas chromatography-mass spectrometry (GC-MS). The contents of volatile compounds such as isoamyl alcohol, ethyl caprylate, ethyl decanoate, ethyl hexanoate, and octanoic acid were evidently higher in the mixed NS + VW than single NS + VW groups. Notably, the highest level of volatile compounds was observed in the HMV group. Orthogonal partial least squares-discriminant analysis (OPLS-DA) combined with odor activity value (OAV) showed that HMV fermented wine had more prominent banana-like, apple-like and floral aroma characteristics. Overall, co-fermentation with M. pulcherrima, H. uvarum, and S. cerevisiae promotes the accumulation of volatile compounds, indicating that these strains have the potential to be developed into multi-species starter cultures.